The Objectives of Sharia Management Accounting Information Reporting: Identification of Values and Characteristics - sonhaji sonhaji; Abdul Kadir Usri; Hedher Tuakia (Journal of Accounting, Business and Management (JABM), 2021)
There is an idea to build sharia management accounting starting from constructing the sharia management accounting conceptual framework. The framework has been developed, one of which contains the objectives of sharia management accounting information reporting. This article aims to develop further the objectives of sharia management accounting information reporting to find the value and characteristics of sharia management accounting information. Qualitative research is used in this study. The data in the form of text were analyzed using the reflective method. The analysis uses a quadrant that articulates the objectives of sharia management accounting information reporting with the management hierarchy and the network of value-creating activities. The study found the nature, type, and value of information that should be presented by a sharia management accounting information system.